2020
DOI: 10.17309/tmfv.2020.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pilates on the Intensity of Pain in the Spine of Women of the First Mature age

Abstract: The purpose of the study is to determine the dynamics of pain intensity in different parts of the spine in women of the first mature age under the influence of pilates. Materials and methods. 64 women took part in research. The women were divided into two groups, each of which included 32 people. The study was carried out at the Sokol sports club and the Olimp fitness club in Kiev. We used the questionnaire “Visual analogue scale of pain”.  Results. We measured the level of pain in the cervical, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
(6 reference statements)
1
7
0
1
Order By: Relevance
“…Health-enhancing aquafitness programs are the most popular among women. It has been reported (Urbanová et al, 2010;Kashuba et al, 2020, Yarmak et al, 2018 that water exercise can positively affect the functional state of the musculoskeletal system, development of the respiratory system, and psycho-emotional state. Furthermore, recently there has been observed a growing interest of women interest in aquafitness as a means to recover strength, maintain good athletic performance, and health.…”
Section: Introductionmentioning
confidence: 99%
“…Health-enhancing aquafitness programs are the most popular among women. It has been reported (Urbanová et al, 2010;Kashuba et al, 2020, Yarmak et al, 2018 that water exercise can positively affect the functional state of the musculoskeletal system, development of the respiratory system, and psycho-emotional state. Furthermore, recently there has been observed a growing interest of women interest in aquafitness as a means to recover strength, maintain good athletic performance, and health.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of correction of postural disorders of different population groups by means of health fitness has been repeatedly raised in scientific circles (Kashuba, Tomilina, Byshevets, Khrypko, Stepanenko, Grygus, Smoleńska, & Savliuk, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis Н0 about the conformity of data to the normal distribution law was checked using the Shapiro-Wilk consistency criterion W (Kashuba, Tomilina et al, 2020). Since the statistical processing revealed that the samples formed from the studied indicators did not correspond to the normal distribution law, the average indicators of work experience, age and intensity of musculoskeletal pain are presented in the form of median and interquartile range Ме (25; 75).…”
Section: Discussionmentioning
confidence: 99%